The diversity of Nilaparvata lugens, Sogatella furcifera and Nephotettix virescens in Pekan Kandang, Melaka / Syazierra Fazanny Wahid - Wahid, Syazierra Fazanny (Faculty of Plantation and Agrotechnology, 2019)
A study on population trend of N. lugens, S. furcifera and N. virescens was conducted at paddy field in Pekan Kandang, Melaka within August to October 2018. The aim of this study is to identify the population ecology of N. lugens, S. furcifera and N. virescens in paddy field with different time of sampling. Yellow sticky trap and yellow pan trap were used to trap the insect pests either in their nymph or adult stage, once a week. The traps were setting up randomly at 1m2 of area in 10 different plots of 20 acres of paddy field. The result shows the normal distribution of the population of insect pests at the paddy field. Descriptive analysis showed regression of r2 for N. lugens, S. furcifera and N. virescens which are 6.2%, 12.1% and 13.2% respectively in different time of sampling. At the end of this study, it was proved that the population of N. lugens, S. furcifera and N. virescens were existed at the paddy field.